Asymmetry controlled dynamic behavior of autonomous chemiluminescent Janus microswimmers. Issue 28 (7th July 2020) - Salinas, Gerardo; Dauphin, Alice L.; Voci, Silvia; Bouffier, Laurent; Sojic, Neso; Kuhn, Alexander
Abstract : Asymmetrically modified Janus microparticles are presented as autonomous light emitting swimmers with shape-controlled trajectories. Abstract : Asymmetrically modified Janus microparticles are presented as autonomous light emitting swimmers. The localized dissolution of hybrid magnesium/polymer objects allows combining chemiluminescence with the spontaneous production of H2 bubbles, and thus generating directed motion. These light-emitting microswimmers are synthesized by using a straightforward methodology based on bipolar electromilling, followed by indirect bipolar electrodeposition of an electrophoretic paint. An optimization of the experimental parameters enables in the first step the formation of well-defined isotropic or anisotropic Mg microparticles. Subsequently, they are asymmetrically modified by wireless deposition of an anodic paint. The degree of asymmetry of the resulting Janus particles can be fine-tuned, leading to a controlled directional motion due to anisotropic gas formation. This autonomous motion is coupled with the emission of bright orange light when Ru(bpy)3 2+ and S2 O8 2− are present in the solution as chemiluminescent reagents. The light emission is based on an original process of interfacial redox-induced chemiluminescence, thus allowing an easy visualization of the swimmer trajectories.